Fortification of Mung bean (Vigna radiata) and Ear mushroom (Auricularia auricula-judae) in dried sago noodles - Donowati Tjokrokusumo; Fiqi Cahyani Octaviani; Raskita Saragih (Microbiology Division, Research Center for Biology, Indonesian Institute of Sciences, 2019)
This study aimed to obtain a formula dried sago noodles enriched with mung beans and ear mushrooms to produce noodles with high protein and fiber content and favored by the panelist. The experimental design used in this study was a Randomized Block Design (RCBD) with two factorial (3×3). Factor A is the percentage of mung bean flour which consists of three levels: a1 = 12%, a2 = 15%, a3 = 18%. Factor B is the percentage of ear mushroom flour consisting of three levels: b1 = 1%, b2 = 2% and b3 = 3%, with 2 replications. The organoleptic testing was done by 30 untrained panelists. The results showed that the most preferred panelists are dried noodles sago enriched with 12% mung bean flour and 1% ear mushroom flour. The resulting product has an overall value of 14 consisting of an average value of color 3.73 (ordinary-like), aroma preference value 3.3 (ordinary-like), texture preference value 3.47 (ordinary-like), and taste preference value 3.50 (ordinary-like).